Analysis of Directive Speech Acts on Megan Bernadette's Characters in The Movie of "The Slumber Party" - Dewi, Mita Sari; Prihandini, Asih (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2024)
The research entitled Analysis of directive speech acts on Megan Barnadette’s character in the movie “The Slumber Party” aims to describe the type of speech acts and the meaning of those speech acts in the movie “The Slumber Party”. The main character’s speech, Megan Bernadette, was utilized as the research data. The study first watched the movie thoroughly to understand the main character in “The Slumber Party.” The second step was for the researcher to read the downloaded movie script, adapt it to the main character’s speech, and note the potential data to be collected. The data were then selected, and the relevant data were analyzed. The data was analyzed based on Yule’s directive speech acts classification theory. According to Yule, the classification of directive speech acts consists of : commands, orders, requests, and giving advice. This research uses a descriptive qualitative research method. The results of this study are data in the form of directive speech acts in the type of “ordering” eleven times, directive speech functions “requesting” five times, and speech acts “giving advice” thirteen times. Directive speech acts on the main character of the movie The Slumber is more dominant in using the directive speech act function of “giving advice”.